Implementation of Physical Education Learning in Public Junior High Schools during the Covid 19 Pandemic in Lubuklinggau City - Tri Turnadi; Muhammad Kristiawan; Rambat Nur Sasongko; Bogy Restu Ilahi (UNIB Press, 2021)
Research on the implementation of physical education learning at State Junior High Schools during the Covid 19 pandemic in Lubuklinggau City. The subjects of this study involved physical education teachers and students in state junior high schools in Lubuklinggau City. The data analysis technique used a qualitative descriptive analysis. Collecting data using observation, questionnaires, and interviews. Based on the results of the research data analysis above, it can be seen from the implementation of Physical Education learning at State Junior High Schools during the Covid 19 pandemic in Lubuklinggau City, which has a percentage of (50.20%) for Physical Education teachers with moderate criteria and for students (67.03%) with criteria good. The results obtained through observation, questionnaires and interviews.